Pills or Sleep Deprivation? Sleep-Deprivation as a Therapeutic Option Intervention in Psychiatry - Antsyborov A. V., Dubatova I. V., Kalinchuk A. V. (Interactive science, 2020)
in recent decades, sleep deprivation has evolved from a single experimental data set to the status of an effective and affordable therapeutic intervention used in daily clinical practice. The mechanism of action of this method is aimed at the same neurotransmitter systems and brain regions as antidepressants. As in the case of pharmacotherapy for sleep deprivation, it should be used under close supervision of a physician. Clinical effects with sleep deprivation are achieved much faster than with psychopharmacotherapy, but they are not long-term in nature. It is possible to improve the results using a combination of pharmacotherapy and sleep deprivation. The use of sleep deprivation in clinical conditions is aimed primarily at preventing depression and its recurrence, as well as in cases resistant to pharmacotherapy. In modern conditions, the method of sleep deprivation is a significant alternative to traditional approaches to therapy of depression.
Keywords: депрессия; depression; депривация сна; sleep deprivation; mechanism of action; clinical effect; механизм действия; клинический эффект